Conceptual modeling of device-independent Web applications - Gomez, J.; Cachero, C.; Pastor, O. (IEEE multimedia, 2001)
Existing tools for building and deploying complex Web sites are inadequate for dealing with the software production process that involves connecting with underlying logic in a unified and systematic way. As a solution, we propose the OO-H method, an object-oriented software approach that captures relevant properties involved in modeling and implementing Web application interfaces.